Pedigree analysis of glucose-6 phosphate dehydrogenase (G6PD) deficiency of a Javanese Chinese family in Indonesia - IDG Ugrasena; Taku Shirakawa; Kaoru Nishiyama; Masafumi Matsuo (Paediatrica Indonesiana, 2001)
The molecular and pedigree analyses in a Javanese Chinese family were carried oul on glucose-6-phosphate dehydrogenase deficiencies. By method of Â MPTP scanning without the sequencing steps, those variants could be confirmed. Two out of three sons were clinically jaundiced at birth due to G6PD deficiency and identified to have a G to T nucleotide change al 1376th nucleotide 01 the G6PD gene (GI376T), corresponding to G6PD Canton. Another son was also identified to have a C to T nucleotide change at 1311st nucleotide 01 the G6PD gene (CI311T), corresponding to a Silent mutation. Their father was normal, but their mother obsorved to have the heleromutation 01 G1376T (G6PD Canton and C1311T (a Silent mutation).